Kinetic model of hydrogenation of glucose to sorbitol on a Ni/Bentonite catalyst - Pandya, Harmitkumar; Vinod, Chathakudath Prabhakaran; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Industrial and Engineering Chemistry Research, 2024)
In the present work, we studied the hydrogenation of glucose to sorbitol using a nickel/bentonite catalyst. The Ni/bentonite catalyst was prepared by the wet impregnation method and characterized by different methods to understand the catalyst surface morphology, surface area, metal content, pore size, etc. Different reaction parameters such as temperature, hydrogen pressure, metal loading, catalyst loading, and agitation speed were studied to achieve a glucose conversion of 96.8% and a sorbitol selectivity of 95.3%. The reusability test was performed to examine the stability of the catalyst. The kinetic models such as the Eley-Rideal and Langmuir-Hinshelwood-Hougen-Watson models were used to study the hydrogenation of glucose and activation energy required for the reaction.